Clinical Characteristics and Survival Analysis in Frequent Alcohol Consumers With COVID-19 - Alberca, Ricardo Wesley; Rigato, Paula Ordonhez; Ramos, Yasmim Álefe Leuzzi; Teixeira, Franciane Mouradian Emidio; Branco, Anna Cláudia Calvielli; Fernandes, Iara Grigoletto; Pietrobon, Anna Julia; Duarte, Alberto Jose da Silva; Aoki, Valeria; Orfali, Raquel Leão; Sato, Maria Notomi (Frontiers in Nutrition, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection can generate a systemic disease named coronavirus disease – 2019 (COVID-19). Currently, the COVID-19 pandemic killed millions worldwide, being huge health and economic challenge worldwide. Several risk factors have been associated with poor disease progression and outcomes, such as age, co-infections, metabolic syndrome, and smoking. Alcohol drinking is a common social practice among adults, but frequent and/or excessive consumption can mitigate the anti-viral and anti-bacterial immune responses. Therefore, we investigated if patients with self-reported daily alcohol consumption (DAC) presented alteration in the immune response to SARS-CoV-2. We investigated 122 COVID-19 patients (101 male and 46 females), in which 23 were DAC patients (18 men and 5 women) and 99 were non-DAC patients (58 men and 41 women), without other infections, neoplasia, or immunodeficiencies. Although no difference in age, DAC patients presented an increase in severity-associated COVID-19 markers such as C-reactive protein, neutrophil count, and neutrophil-to-lymphocyte ratio. Also, DAC patients presented a reduction in the lymphocytes and monocytes counts. Importantly, DAC group presented an increase in death rate in comparison with non-DAC group. Our results demonstrated that in our cohort DAC enhanced COVID-19-associated inflammation, and increased the death due to COVID-19.